EXPERIMENTAL INVESTIGATION ON EFFECT OF HIGH TEMPERATURE ON M-20 GEOPOLYMER CONCRETE - Mr. Sanket P. Kulkarni; Miss. Smita M. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
Concrete is one of the most widely used construction material. The global use of cement concrete is second only to the use of water. The demand for concrete as a construction material is increasing day to day. The production process of cement releases some harmful substances, which adversely effect on environment. Design and experimental investigation on development of geopolymer concrete is important because increase in use of geopolymer concrete leads to reduction in use of regular cement concrete and ultimately production of cement. Also the fly ash and ground granulated blast furnace slag is used and the problem of dumping of these materials ultimately gets solved.